Drill and Practice Methods: Peningkatan Kemampuan Menghafal Surah Al-Fatihah pada Siswa MIN Buol - Farmi Uswah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to improve memorization of Surah Al-Fatihah in MIN Buol students. The subject of the study was a student in class III MIN Buol. The study uses the Class Action method through two cycles that include planning, execution, observation, and reflection activities. The results showed that drill and practice methods can improve students' ability to memorize Surah Al-Fatihah. The increase in student learning outcomes in pre-cycles by 66.61% to 80.68% in cycle I, and increased quite significantly to 91.43 in cycle II. The classical completion value of 64.82% also increased to 78.36% in cycle I, and increased quite significantly by 88.57% in cycle II. Drill and practice methods can improve students' learning outcomes and ability to memorize short surahs in the Quran. Drill and practice methods can be applied to Madrasah Ibtidaiyah students.